THE MODERATING ROLE OF HALAL CULTURE LINKING HALAL ORIENTATION STRATEGIES WITH THE FIRM’S FINANCIAL PERFORMANCE: A STUDY OF HALAL FOOD FIRMS IN THAILAND - Mahamud, Tosaporn; Yama, Arifeen (Asian Crime and Society Review, 2021)
Though the halal orientation strategy (HOS) has a critical role to play for preserving the products halal status. However, there is a lack of halal orientation strategy literature affecting halal companies’ financial performance (FP). As a result, the primary objective of all firms is to optimize profits, this study explores the effect of HOS on the FP and the moderator of halal culture (HC) in halal food companies (HFC) in Thailand. Data from 164 hall-food companies in Thailand were obtained and analyzed using the PLS-SEM technique. Studies have shown that halal production has a negative impact, while transformation, halal storage and halal materials have a positive effect on FP. Furthermore, halal culture moderates the link among production and FP of a company. The findings will allow HFC executives to improve their FP by financing in HOP, hence paying more attentions to the halal community. Therefore, it assists policymakers recognize the value of the revision of halal certification criteria. This study also helps to increase awareness of the HOP relationship to the FP of HFC.